Features of development of flexibility for girls 5–7 years aged, engaged in a calisthenics - Войнаровська, Г. А. (Slobozhanskyi Herald of Science and Sport, 2011)
Mobility of spine, humeral, hip and talocrural joints of girls 5–7 years is researched. The researched girls had a different level of development of flexibility (coefficients of variation from 17,1 to 99,7 %). It is set: mobility in humeral joints for certain is associate with mobility of spine during unbending; the presence of connection is educed in both groups between the equilibrium of 90о and 180о and mobility in thurls (p<0,05), between the equilibrium of 180о and mobility of spine at bending, between the equilibrium of 90о and dynamic force of hands, that it is necessary to take into account young gymnasts in a training process.